2011
DOI: 10.1001/archdermatol.2011.228
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Dermatologist Migration Patterns After Residency Training

Abstract: To evaluate the migration patterns of dermatologists from residency training to eventual clinical practice to assess whether certain programs or regions were more likely to populate their own areas with graduates. Design: Analysis of existing data from the American Academy of Dermatology's membership database. Setting: The United States and Puerto Rico. Participants: Graduates of US dermatology residency programs completing training before 2005 and actively practicing in 2009. Data from 7067 practicing dermato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 15 publications
(13 reference statements)
1
11
0
Order By: Relevance
“…Primary care specialties have shown better retention of their Southern residency graduates than the other regions, a finding that was confirmed in this study as well [13]. Interestingly, our data revealed that the MW both retains a significant portion of their recent residency graduates and receives a significant portion of graduates from the NE and West, which is contrary to what has been reported in other studies both in and outside dermatology [2,13]. However, the study by Resneck and Kostecki, which demonstrated poor MW retention of trainees, only surveyed dermatologists that completed residency prior to 2005.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Primary care specialties have shown better retention of their Southern residency graduates than the other regions, a finding that was confirmed in this study as well [13]. Interestingly, our data revealed that the MW both retains a significant portion of their recent residency graduates and receives a significant portion of graduates from the NE and West, which is contrary to what has been reported in other studies both in and outside dermatology [2,13]. However, the study by Resneck and Kostecki, which demonstrated poor MW retention of trainees, only surveyed dermatologists that completed residency prior to 2005.…”
Section: Discussionsupporting
confidence: 61%
“…An annual survey was administered between 2008 and 2013 to participants of the board examination review courses organized by Galderma Laboratories in August or September of each year. The anonymous survey instrument is exempt from institutional review board monitoring under Federal Register regulation 56 FR 28012, 28021, Subpart A, Section 97.101(b) (2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond factors examined in this study, regional differences in the organization of healthcare delivery or the health insurance market may contribute to this pitcture. Lastly, similarities between neighboring states described above may be a reflection of similarities in medical training, which does not only affect medical decision making, forming a culture of medical reasoning and decision-making, but also practice locations, as the majority of physicians choose practices in relatively close proximity to the location of their residency 5,6…”
Section: Discussionmentioning
confidence: 99%
“…During our most recent site visit by the dermatology residency review committee site visitor, this research program for dermatology residents received several positive comments and a request that this information be disseminated to other dermatology residency programs. Although most of our residents enter private dermatology practices more than 100 miles from Galveston,19 the additional dimension in research training during dermatology residency adds to their depth of experience in the specialty. In addition, the adoption of the scholarly project requirement has resulted in a cultural shift within the department that is more supportive of and enthusiastic for dermatology research by the residents and faculty.…”
Section: Discussionmentioning
confidence: 99%